2018
DOI: 10.7547/16-033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on the Antibiotic Resistance of Bacteria Recovered from Diabetic Foot Ulcer Fluid

Abstract: These findings highlight the importance of a more comprehensive understanding of the conditions in DFUs to inform clinical decision making in the selection and application of antibiotics in treating these difficult-to-heal wounds. The scale of the differences in the efficacies of antibiotics at the different pH values examined is likely to be sufficient to suggest reconsideration of the antibiotics of choice in the treatment of DFU infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The wound environment of DFUs is significantly more alkaline than acute wounds, contributing to the complex host–microbiome interaction. In a test of different bacterial strains, including Pseudomonas , alkaline pH conditions increased biofilm formation [ 83 ], with pH also exhibiting differential effects on bacterial resistance to antibiotics [ 84 ]. Considering antibiotic resistance testing generally occurs near physiological pH, this difference in bacterial sensitivity should be accounted for when prescribing treatment for an infection found in an abnormally alkaline DFU environment.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…The wound environment of DFUs is significantly more alkaline than acute wounds, contributing to the complex host–microbiome interaction. In a test of different bacterial strains, including Pseudomonas , alkaline pH conditions increased biofilm formation [ 83 ], with pH also exhibiting differential effects on bacterial resistance to antibiotics [ 84 ]. Considering antibiotic resistance testing generally occurs near physiological pH, this difference in bacterial sensitivity should be accounted for when prescribing treatment for an infection found in an abnormally alkaline DFU environment.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…In an in vitro study on DFU samples, McArdle et al showed an increased resistance toward ciprofloxacin for both P. aeruginosa and S. aureus . P. aeruginosa was more resistant under acidic conditions under which alkaline ones were more favorable for the increased resistance of S. aureus [ 123 ].…”
Section: Crosstalk Between Species In Chronic Woundsmentioning
confidence: 99%
“…Diabetic wound pH is impacted by these pathophysiological particularities. In contrast to the acidic pH in acute wounds of about 5.5, diabetic wound pH reaches values in the neutral and alkaline range of up to pH 8.5 in patients with diabetes and animal models of diabetes. The high wound pH is likely related to low-grade chronic inflammation and leakage of physiological fluids, which are at slightly alkaline pH, into the chronic wounds. , …”
Section: Recently Emerged Diagnostic Targetsmentioning
confidence: 99%
“…Bacterial infection elicits an inflammatory response and leads to the upregulation of pro-inflammatory cytokines, ROS, and products of glycolysis such as lactate . Wound pH is also associated with wound healing, as the basic and slightly alkaline pH found in diabetic wounds promotes the growth of pathogenic bacteria. …”
Section: Recently Emerged Diagnostic Targetsmentioning
confidence: 99%